Combining enyne metathesis with long-established organic transformations: a powerful strategy for the sustainable synthesis of bioactive molecules - Dragutan, Valerian; Dragutan, Ileana; Demonceau, Albert; Delaude, Lionel (Beilstein Journal of Organic Chemistry, 2020)
This account surveys the current progress on the application of intra- and intermolecular enyne metathesis as main key steps in the synthesis of challenging structural motifs and stereochemistries found in bioactive compounds. Special emphasis is placed on ruthenium catalysts as promoters of enyne metathesis to build the desired 1,3-dienic units. The advantageous association of this approach with name reactions like Grignard, Wittig, Diels–Alder, Suzuki–Miyaura, Heck cross-coupling, etc. is illustrated. Examples unveil the generality of such tandem reactions in providing not only the intricate structures of known, in vivo effective substances but also for designing chemically modified analogs as valid alternatives for further therapeutic agents.
Keywords: bioactive compounds; enyne metathesis; ring-closing metathesis; ruthenium catalysts; tandem reactions

Handbook of Metathesis - Grubbs, R. H.; Wenzel, A. G.; O'Leary, D. J.; Khosravi, E. (Wiley-VCH, 2015)

Olefin Metathesis: Theory and Practice - Grela, K. (John Wiley & Sons, 2014)

(untitled) - Ogba, O. M.; Warner, N. C.; O’Leary, D. J.; Grubbs, R. H. (Chem. Soc. Rev., 2018)

(untitled) - Ehrhorn, H.; Schlösser, J.; Bockfeld, D.; Tamm, M. (Beilstein J. Org. Chem., 2018)

(untitled) - Cheng-Sánchez, I.; Sarabia, F. (Synthesis, 2018)

(untitled) - Żak, P.; Pietraszuk, C. (Beilstein J. Org. Chem., 2019)

(untitled) - Gong, J.; Li, W.; Fu, P.; MacMillan, J.; De Brabander, J. K. (Org. Lett., 2019)

(untitled) - Nocquet, P.-A.; Macé, A.; Legros, F.; Lebreton, J.; Dujardin, G.; Collet, S.; Martel, A.; Carboni, B.; Carreaux, F. (Beilstein J. Org. Chem., 2018)

(untitled) - Guo, Z.; Hong, S. Y.; Wang, J.; Rehan, S.; Liu, W.; Peng, H.; Das, M.; Li, W.; Bhat, S.; Peiffer, B.; Ullman, B. R.; Tse, C.-M.; et al. (Nat. Chem., 2019)

(untitled) - Chattopadhyay, S. K.; Ghosh, S.; Sil, S. (Beilstein J. Org. Chem., 2018)

(untitled) - Wu, Q.; Rauscher, P. M.; Lang, X.; Wojtecki, R. J.; de Pablo, J. J.; Hore, M. J. A.; Rowan, S. J. (Science, 2017)

(untitled) - Schultze, C.; Schmidt, B. (Beilstein J. Org. Chem., 2018)

(untitled) - Yu, M.; Lou, S.; Gonzalez-Bobes, F. (Org. Process Res. Dev., 2018)

(untitled) - Erak, M.; Bellmann-Sickert, K.; Els-Heindl, S.; Beck-Sickinger, A. G. (Bioorg. Med. Chem., 2018)

(untitled) - Dragutan, I.; Dragutan, V.; Mitan, C.; Vosloo, H. C. M.; Delaude, L.; Demonceau, A. (Beilstein J. Org. Chem., 2011)

(untitled) - Liang, Y.; Zeng, F.-R.; Li, Z.-L. (Curr. Org. Synth., 2019)

(untitled) - Dutertre, F.; Bang, K.-T.; Vereroudakis, E.; Loppinet, B.; Yang, S.; Kang, S.-Y.; Fytas, G.; Choi, T.-L. (Macromolecules, 2019)

(untitled) - Dragutan, I.; Dragutan, V.; Fischer, H. (J. Inorg. Organomet. Polym. Mater., 2008)

(untitled) - Dragutan, V.; Dragutan, I.; Fischer, H. (J. Inorg. Organomet. Polym. Mater., 2008)

(untitled) - Le, D.; Samart, C.; Tsutsumi, K.; Nomura, K.; Kongparakul, S. (ACS Omega, 2018)

(untitled) - Mu, Y.; Nguyen, T. T.; van der Mei, F. W.; Schrock, R. R.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Szczepaniak, G.; Nogaś, W.; Piątkowski, J.; Ruszczyńska, A.; Bulska, E.; Grela, K. (Org. Process Res. Dev., 2019)

(untitled) - Martinez-Amezaga, M.; Delpiccolo, C. M. L.; Méndez, L.; Dragutan, I.; Dragutan, V.; Mata, E. G. (Catalysts, 2017)

(untitled) - Yasir, M.; Liu, P.; Tennie, I. K.; Kilbinger, A. F. M. (Nat. Chem., 2019)

(untitled) - Sabatino, V.; Ward, T. R. (Beilstein J. Org. Chem., 2019)

(untitled) - Kim, C.; Ondrusek, B. A.; Chung, H. (Org. Lett., 2018)

(untitled) - Schmid, T. E.; Dumas, A.; Colombel-Rouen, S.; Crévisy, C.; Baslé, O.; Mauduit, M. (Synlett, 2017)

(untitled) - Tomasek, J.; Schatz, J. (Green Chem., 2013)

(untitled) - Wang, W.; Cui, L.; Sun, P.; Shi, L.; Yue, C.; Li, F. (Chem. Rev., 2018)

(untitled) - Gułajski, Ł.; Tracz, A.; Urbaniak, K.; Czarnocki, S. J.; Bieniek, M.; Olszewski, T. K. (Beilstein J. Org. Chem., 2019)

(untitled) - Xu, C.; Shen, X.; Hoveyda, A. H. (J. Am. Chem. Soc., 2017)

(untitled) - Etsè, K. S.; Ngendera, A.; Ntumba, N. T.; Demonceau, A.; Delaude, L.; Dragutan, I.; Dragutan, V. (Curr. Med. Chem., 2017)

(untitled) - Pollini, J.; Bragoni, V.; Gooßen, L. J. (Beilstein J. Org. Chem., 2018)

(untitled) - Dassonneville, B.; Delaude, L.; Demonceau, A.; Dragutan, I.; Dragutan, V.; Etsè, K. S.; Hans, M. (Curr. Org. Chem., 2013)

(untitled) - Bicchielli, D.; Borguet, Y.; Delaude, L.; Demonceau, A.; Dragutan, I.; Dragutan, V.; Hans, M.; Jossifov, C.; Nicks, F.; Willem, Q. (Curr. Org. Synth., 2012)

(untitled) - Fuwa, H.; Sasaki, M. (Bull. Chem. Soc. Jpn., 2016)

(untitled) - Meek, S. J.; O’Brien, R. V.; Llaveria, J.; Schrock, R. R.; Hoveyda, A. H. (Nature, 2011)

(untitled) - Benke, Z.; Nonn, M.; Kardos, M.; Fustero, S.; Kiss, L. (Beilstein J. Org. Chem., 2018)

(untitled) - Yu, M.; Schrock, R. R.; Hoveyda, A. H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Montgomery, T. P.; Ahmed, T. S.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2017)

(untitled) - Montgomery, T. P.; Johns, A. M.; Grubbs, R. H. (Catalysts, 2017)

(untitled) - Lekky, A.; Ruengsatra, T.; Ruchirawat, S.; Ploypradith, P. (J. Org. Chem., 2019)

(untitled) - Müller, D. S.; Curbet, I.; Raoul, Y.; Le Nôtre, J.; Baslé, O.; Mauduit, M. (Org. Lett., 2018)

(untitled) - Kotha, S.; Meshram, M.; Chakkapalli, C. (Beilstein J. Org. Chem., 2018)

Handbook of Metathesis: Applications in Organic Synthesis - Li, J.; Lee, D. (Enyne Metathesis, 2015)

Olefin Metathesis: Theory and Practice - Diver, S. T.; Griffiths, J. R. (Ene-Yne Metathesis, 2014)

(untitled) - Dragutan, I.; Dragutan, V.; Demonceau, A.; Delaude, L. (Curr. Org. Chem., 2013)

(untitled) - Li, J.; Lee, D. (Eur. J. Org. Chem., 2011)

(untitled) - Mori, M. (Materials, 2010)

(untitled) - Datta, R.; Ghosh, S. (Beilstein J. Org. Chem., 2018)

(untitled) - Kotha, S.; Chavan, A. S.; Goyal, D. (ACS Omega, 2019)

(untitled) - Zhao, Y.; Hoveyda, A. H.; Schrock, R. R. (Org. Lett., 2011)

(untitled) - Feng, L.; Wang, Y.; Yuan, S.; Wang, K.-Y.; Li, J.-L.; Day, G. S.; Qiu, D.; Cheng, L.; Chen, W.-M.; Madrahimov, S. T.; Zhou, H.-C. (ACS Catal., 2019)

(untitled) - Badshah, S. L.; Ullah, A.; Ahmad, N.; Almarhoon, Z. M.; Mabkhot, Y. (Molecules, 2018)

(untitled) - Jolliffe, H. G.; Diab, S.; Gerogiorgis, D. I. (Org. Process Res. Dev., 2018)

(untitled) - Tang, X.; Demiray, M.; Wirth, T.; Allemann, R. K. (Bioorg. Med. Chem., 2018)

(untitled) - Vil’, V. A.; Yaremenko, I. A.; Ilovaisky, A.; Terent’ev, A. O. (Molecules, 2017)

(untitled) - Triemer, S.; Gilmore, K.; Vu, G. T.; Seeberger, P. H.; Seidel-Morgenstern, A. (Angew. Chem., Int. Ed., 2018)

(untitled) - Horváth, Z.; Horosanskaia, E.; Lee, J. W.; Lorenz, H.; Gilmore, K.; Seeberger, P. H.; Seidel-Morgenstern, A. (Org. Process Res. Dev., 2015)

(untitled) - Gilmore, K.; Kopetzki, D.; Lee, J. W.; Horváth, Z.; McQuade, D. T.; Seidel-Morgenstern, A.; Seeberger, P. H. (Chem. Commun., 2014)

(untitled) - Cook, S. P. (Future Med. Chem., 2013)

(untitled) - Tiwari, M. K.; Chaudhary, S. (Med. Res. Rev., 2020)

(untitled) - Zhu, C.; Cook, S. P. (J. Am. Chem. Soc., 2012)

(untitled) - Kopetzki, D.; Lévesque, F.; Seeberger, P. H. (Chem. – Eur. J., 2013)

(untitled) - Lévesque, F.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2012)

(untitled) - Wang, Y.; Feng, L.; Pang, J.; Li, J.; Huang, N.; Day, G. S.; Cheng, L.; Drake, H. F.; Wang, Y.; Lollar, C.; Qin, J.; Gu, Z.; et al. (Adv. Sci., 2019)

(untitled) - Oguri, H. (Chem. Rec., 2016)

(untitled) - Oguri, H.; Hiruma, T.; Yamagishi, Y.; Oikawa, H.; Ishiyama, A.; Otoguro, K.; Yamada, H.; O̅mura, S. (J. Am. Chem. Soc., 2011)

(untitled) - Chang, L.; Jiang, H.; Fu, J.; Liu, B.; Li, C.-c.; Yang, Z. (J. Org. Chem., 2012)

(untitled) - Kim, C. H.; An, H. J.; Shin, W. K.; Yu, W.; Woo, S. K.; Jung, S. K.; Lee, E. (Angew. Chem., Int. Ed., 2006)

(untitled) - Ko, H. M.; Lee, C. W.; Kwon, H. K.; Chung, H. S.; Choi, S. Y.; Chung, Y. K.; Lee, E. (Angew. Chem., Int. Ed., 2009)

(untitled) - Trost, B. M.; Bai, W.-J.; Stivala, C. E.; Hohn, C.; Poock, C.; Heinrich, M.; Xu, S.; Rey, J. (J. Am. Chem. Soc., 2018)

(untitled) - Fürstner, A.; Bouchez, L. C.; Morency, L.; Funel, J.-A.; Liepins, V.; Porée, F.-H.; Gilmour, R.; Laurich, D.; Beaufils, F.; Tamiya, M. (Chem. – Eur. J., 2009)

(untitled) - Fürstner, A.; Kattnig, E.; Kelter, G.; Fiebig, H.-H. (Chem. – Eur. J., 2009)

(untitled) - Fürstner, A.; Flügge, S.; Larionov, O.; Takahashi, Y.; Kubota, T.; Kobayashi, J. (Chem. – Eur. J., 2009)

(untitled) - Kitamura, T.; Sato, Y.; Mori, M. (Tetrahedron, 2004)

(untitled) - Pena, M. R.; Stille, J. K. (J. Am. Chem. Soc., 1989)

(untitled) - Knüppel, S.; Rogachev, V. O.; Metz, P. (Eur. J. Org. Chem., 2010)

(untitled) - Wang, Y.; Darweesh, A. F.; Zimdars, P.; Metz, P. (Beilstein J. Org. Chem., 2019)

(untitled) - Cesati, R. R., III; de Armas, J.; Hoveyda, A. H. (J. Am. Chem. Soc., 2004)

(untitled) - Satcharoen, V.; McLean, N. J.; Kemp, S. C.; Camp, N. P.; Brown, R. C. D. (Org. Lett., 2007)

(untitled) - Schubert, M.; Metz, P. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ramharter, J.; Weinstabl, H.; Mulzer, J. (J. Am. Chem. Soc., 2010)

(untitled) - Jakubec, P.; Hawkins, A.; Felzmann, W.; Dixon, D. J. (J. Am. Chem. Soc., 2012)

(untitled) - Toma, T.; Kita, Y.; Fukuyama, T. (J. Am. Chem. Soc., 2010)

(untitled) - Clark, J. S.; Townsend, R. J.; Blake, A. J.; Teat, S. J.; Johns, A. (Tetrahedron Lett., 2001)

(untitled) - Jung, M. E.; Yoo, D. (Org. Lett., 2011)

(untitled) - Jung, M. E.; Chu, H. V. (Org. Lett., 2008)

(untitled) - Jung, M. E.; Chu, H. V. (Tetrahedron Lett., 2011)

(untitled) - Wei, H.; Qiao, C.; Liu, G.; Yang, Z.; Li, C.-c. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kress, S.; Weckesser, J.; Schulz, S. R.; Blechert, S. (Eur. J. Org. Chem., 2013)

(untitled) - Vanga, D. G.; Kaliappan, K. P. (Synlett, 2012)

(untitled) - Subrahmanyam, A. V.; Palanichamy, K.; Kaliappan, K. P. (Chem. – Eur. J., 2010)

(untitled) - Cook, C.; Guinchard, X.; Liron, F.; Roulland, E. (Org. Lett., 2010)